2018
DOI: 10.1007/s00127-018-1608-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of media reports of severe mental illness on stigma and discrimination, and interventions that aim to mitigate any adverse impact

Abstract: Purpose: This review aims to summarise the evidence on the impact of news media and social media reports of severe mental illness (SMI) on stigma, and interventions that aim to mitigate any adverse impact. Methods: A systematic search of electronic databases was conducted in December 2017 to identify studies that report on the impact of media coverage or media interventions on stigma related to schizophrenia, psychosis, bipolar disorder, or mental illness in general. Data were synthesised narratively. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 49 publications
0
74
0
1
Order By: Relevance
“…Studies have consistently shown that both entertainment and news media provide overwhelmingly dramatic and distorted images of mental illness that emphasize dangerousness, criminality and unpredictability, and employers and supervisors are exposed to these influences as well. A recent review concluded that destigmatizing interventions targeting media professionals should be a research priority [24]. Entertainment and news media model negative reactions to people with mental illness, including fear, rejection, derision and ridicule [23].…”
Section: Social Stigma Definedmentioning
confidence: 99%
“…Studies have consistently shown that both entertainment and news media provide overwhelmingly dramatic and distorted images of mental illness that emphasize dangerousness, criminality and unpredictability, and employers and supervisors are exposed to these influences as well. A recent review concluded that destigmatizing interventions targeting media professionals should be a research priority [24]. Entertainment and news media model negative reactions to people with mental illness, including fear, rejection, derision and ridicule [23].…”
Section: Social Stigma Definedmentioning
confidence: 99%
“…Namely, the media can serve to promote products and shape behaviors predominantly of young people (Romer & Moreno, 2017). Numerous studies also highlight the impact of the media on the perception of illnesses, stigma, mental distress and violent behavior (Ross et al, 2019;Williams & Witte, 2018;Wormwood, Wormwood, Lin, Lynn, Barrett, & Quigley, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is mainly gathered from negative examples, where digital media have served as a vehicle for marketing and social transmission of risky products and behaviours (Romer & Moreno, 2017), with adolescents and young adults serving as common victims, due to their increased exposure and unique vulnerability to the effects of social media in particular, and digital communication in general (Lenhart, 2016). In addition, much of the recent works analyse the media impact on severe mental illnesses and associated outcomes like stigma (Ross, Morgan, Jorm, & Reavley, 2019), suicide (Williams & Witte, 2018), violence (Wormwood, Lin, Lynn, Barrett, & Quigley, 2019), hostility (Adeline & Schumacher, 2018), or body image (Rounsefel, et al, 2019). This stems from the fact that the media coverage of mental health care issues, as an outstanding research area with long-standing impact on public opinion and governmental policies, has a long history of repeated scientific interest and conducted empirical research (Ross et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries have renamed schizophrenia to diminish its associated stigma, however with little evidence for effectiveness [58]. The impact of social media on stigma remains also insufficiently explored [38,59]. A recent review has shown small to medium effects of contact interventions, educational interventions, mixed contact and education, family psychoeducation programs, and hallucination simulations and has concluded that it was needed to understand the active ingredients of these interventions to improve their effectiveness [60].…”
Section: Overallmentioning
confidence: 99%